Psychometric analysis of Learning Climate Questionnaire in psychology students from a private university of Arequipa - Arias Gallegos, Walter L. (2019)
The present research, of psychometrical kind, analyses the validity and reliability of the Learning Climate Questionnaire in a simple of 152 university students of Psychology from a private university of Arequipa. The data was processed following the criteria of the classical theory of tests and the factor analyses theory. The results indicate that the test has a structure of one factor only which explains the 54.5% of the total variance, with an internal consistency level of 0.915. We conclude that the test is valid and reliable, but it is necessary to research more with representative samples of different levels of teaching.